Urgensi Pendidikan Karakter Melalui Pembelajaran PKn di SDS IT Cendekia Medan - Abdul Gani Jamora Nasution; Riska Aulia; Alya Rina Armalia Pane; Sindi Antika; Irma Hidayah Batubara (Departement of Mathematics Education, 2023)
Initial observations at Sds It Cendekia Medan revealed that the school had made progress in implementing character education. Each school displays character building values on the classroom walls, encourages students to practice good hygiene before entering class, provides conservation areas, and teaches students to take off their shoes before entering class. The aims of this research are as follows: 1) describe the teacher's knowledge about character education; 2) describe the incorporation of 18 character values into the PKn instruction; and 3) describe the factors that facilitate and hinder the implementation of character education. This research proposal is a qualitative descriptive research. The five phases of descriptive quantitative research are as follows: pre-study planning and design; data collection; reduction and presentation of data; data analysis and interpretation; as well as data verification and validation. Information Gathering Strategies Through Observations, Interviews, and Documentation. The research findings show that taking all things into consideration, the integration of the 18 characters into the Civics curriculum in the second year class of SDS It Cendekia Medan was successful. The results of research on the incorporation of character education into Civics education are included in the successful category; most teachers have a general understanding of character education. Teachers are tasked with shaping the personality of their students by incorporating character values into the classroom experience in all subjects; in return, students are expected to pay attention to their instructors as they present course material and apply the good habits they learn from their teachers into their daily lives at home and at school.